A 61‐year‐old man with erythematous forearm papules three months after liver transplantation. Issue 3 (25th March 2018) - Ayrapetyan, Mesrop; Googe, Paul B.; Jolly, Puneet; Levinson, Kara; Popowitch, Elena; Lachiewicz, Anne M.
Abstract: A 61‐year‐old Caucasian man presented with papules on his left forearm and hand three months after liver transplantation: images from physical exam, pathology, and microbiology are presented. Skin biopsy confirmed the presence of fungal elements within the hair shaft, which is consistent with Majocchi granuloma, also known as nodular granulomatous perifolliculitis. A combination of fungal culture, microscopic morphology, and gene sequencing was used to identify the causative organism. The patient recovered with appropriate systemic antifungal therapy.